Spatial Appraisal of Problems and Prospects of Fertilizer Use for Agriculture on the Environment in Mbieri, Mbaitoli Local Government Area, Imo State Nigeria - L, Chikwendu; E. D, Jenkwe; E. I, Eleazu; C. G, Ogbonna (Review of Environment and Earth Sciences, 2017)
This study appraises the spatial problems and prospects of fertilizer use in agriculture on the Environment in Mbieri, Mbaitoli Local Government Area of Imo State. Structured questionnaires were sampled in each villages randomly selected from the seven autonomous communities of Amaike-Mbieri, Awo Mbieri, Ezi-Mbieri, Ihitte Isi-Mbieri, Obazu Mbieri, Obi-Mbieri and Umueze-Mbieri for collection of data. The data were analysed using descriptive statistical tools of tables, charts and graphs. The outcome showed that 71.2% of the farmers do not have University Education. All the kinds of fertilizer in use in the study area contain Nitrogen with NPK 20-10-10 the most sought-after. Findings show that 54% of the farmers prefer the application of fertilizer NPK for replenishing lost soil nutrients while, 60% of the Farmers in the study area use surface broadcast method in application of fertilizer NPK on their farms. However, it was observed from this research that majority of this nitrogen compounds are washed down through surface runoffs causing pollution and eutrophication of the Ecosystems and water bodies. Government should set up research centre for Fertilizer use in Agriculture where farmers can be equipped with adequate knowledge of the best way to use fertilizer NPK while sustaining the environment.